Update on the consensus of classification systems in distal radius fracture - Enrique Armando Pancorbo Sandoval (ECIMED, 2021)
Introduction: A classification is necessary for the correct orientation of the orthopedic surgeon in terms of differentiating the types of fractures at the distal end of the radius, their prognosis based on their complexity, the importance of radiography, the demographic variables of each case and what type of procedure will be the most suitable for the patient. Objective: To evaluate the current classifications for fractures of the distal end of the radius and to propose on the existing evidence which classification systems have better reliability and reproducibility. Development: The Pubmed / MEDLINE, SciELO, BVS, Scopus, Ebsco and Cochrane databases were searched; the descriptors "distal radius fracture", distal radius fracture classification, wrist fracture were used. , consensus on fracture of the distal end of the radius, radiology in the fracture of the wrist, current therapeutic guidelines for the treatment of distal fractures of the radius, alone and with the following chains "classification", "radiology". 19 original articles, 10 review articles, 4 therapeutic guidelines, 2 research guides, and 2 specialty books were included. Classification systems for distal radius fractures were examined. Conclusions: There is no consensus on the classification system. The poor contribution to the orthopedic of the Frykman classification is verified and that the AO system proves to be easier to interpret. The usefulness of skeletal traction radiography is evidenced for a useful diagnosis and to help the surgeon in making decisions for the treatment of the patient.